Unusual presentation of Pott disease and diagnostic challenges in a resource-limited setting: a case report - Anacret Byamukama; Moses Acan; Mugisha Julius Sebikali (Journal of Medical Case Reports, 2023)
Abstract Background Pott disease is rare and responsible for only 1%–2% of all tuberculosis cases. It poses diagnostic challenges in resource-limited settings due to unusual presentation and limited investigative capacity, resulting in debilitating sequelae if diagnosed late. Case presentation We present a case of severe Pott disease of the lumbar spine, with a large paravertebral abscess tracking down to the gluteal region in a 27-year-old Black African Ugandan woman living with human immunodeficiency virus, whose main complaint was right lower abdominal pain. She was initially misdiagnosed from the peripheral clinics as a case of lumbago and later with a psoas abscess. The diagnosis of severe Pott disease was established at the regional referral hospital following an abdominal computed tomography scan, and the patient was appropriately initiated on anti-tuberculosis drugs. However, only abscess drainage and provision of a lumbar corset were possible, with no neurosurgical intervention done on the spine due to financial constraints. Clinical review at 2, 6, and 12 months revealed improvement. Conclusions Pott disease may present with non-specific symptoms such as abdominal pain resulting from pressure effects of an expansile cold abscess. This, coupled with limited diagnostic capacity in resource-limited settings; results in significant morbidity and possible mortality. Hence, there is need to train clinicians to increase their index of suspicion and equip health units with basic radiological equipment, such as x-ray, for timely detection and subsequent management of Pott disease.